Reinforcements in avian wing bones: Experiments, analysis, and modeling. (December 2017) - Novitskaya, E.; Ruestes, C.J.; Porter, M.M.; Lubarda, V.A.; Meyers, M.A.; McKittrick, J.
Abstract: Almost all species of modern birds are capable of flight; the mechanical competency of their wings and the rigidity of their skeletal system evolved to enable this outstanding feat. One of the most interesting examples of structural adaptation in birds is the internal structure of their wing bones. In flying birds, bones need to be sufficiently strong and stiff to withstand forces during takeoff, flight, and landing, with a minimum of weight. The cross-sectional morphology and presence of reinforcing structures (struts and ridges) found within bird wing bones vary from species to species, depending on how the wings are utilized. It is shown that both morphology and internal features increases the resistance to flexure and torsion with a minimum weight penalty. Prototypes of reinforcing struts fabricated by 3D printing were tested in diametral compression and torsion to validate the concept. In compression, the ovalization decreased through the insertion of struts, while they had no effect on torsional resistance. An elastic model of a circular ring reinforced by horizontal and vertical struts is developed to explain the compressive stiffening response of the ring caused by differently oriented struts.